The association between running injuries and training parameters: a systematic review - Fredette, A.; Roy, J. S.; Perreault, K.; Dupuis, F.; Napier, C.; Esculier, J. F. (Journal of Athletic Training, 2022)
Objective To synthesize the current evidence on the incidence of running-related injuries (RRIs) and their association with training parameters (distance, duration, frequency, intensity), as well as recent changes in training parameters.